The Plot to Destroy Democracy : How Putin and his Spies are Undermining America and Dismantling the West - Nance, Malcolm; Foreword by Reiner, Rob (New York Hachette Books, 2018)
A provocative, comprehensive analysis of Putin and the Russian Federation's master plan to destroy democracy. Includes a foreword by Rob Reiner. In the greatest intelligence operation in the history of the world, Donald Trump was made President of the United States with the assistance of a foreign power. For the first time, The Plot to Destroy Democracy reveals the dramatic story of how blackmail, espionage, assassination, and psychological warfare were used by Vladimir Putin and his spy agencies to steal the 2016 U.S. election-and attempted to bring about the fall of NATO, the European Union and western democracy. It will show how Russia and its fifth column allies tried to flip the cornerstones of democracy in order to reengineer the world political order that kept most of the world free since since 1945. Career U.S. Intelligence officer Malcolm Nance will examine how Russia has used cyberwarfare, political propaganda and manipulating our perception of reality-and will use it again-to weaponize American news, traditional media, social media, and the workings of the internet to attack and break apart democratic institutions from within and what we can expect to come should we fail to stop their next attack. In his 35-year career in intelligence, Nance specialized in cryptology, national security policy, counter-terrorism intelligence.
Include Index
Keywords: Russia (Federation) -- United States -- Presidents--Election